The 10-Year Incidence Trend of Common Cancers at a Referral Hospital in Tehran, Iran From 2007 to 2016 - Hormoz Sanaeinasab; Esmat Davoudi Monfared; Ali-Akbar Karimi Zarchi; Mohsen Saffari; Abdowreza Delavari (Baqiyatallah University of Medical Sciences, 2019)
Background: Common cancers such as colon, breast, and lung cancer are increasing in developing countries. Objective: This study was conducted to determine 10-year trends and changes in common cancers in patients from a referral hospital in Tehran, Iran. Methods: This cross-sectional study investigated a study population comprising colon, stomach, lung, prostate, and breast cancer patients registered at the cancer center of a referral hospital in Tehran, Iran from April 1, 2007 to the end of March, 2016 (n=4472). Inclusion criteria were a definitive diagnosis of cancer and an age between 15 and 75 years. Data was entered into SPSS (version 18) software and analyzed using the Time Series analysis and Scatter IO graph. Results: Significant correlations (P value <0.001) were seen between age increases in patients and the increasing number of patients in any type of cancer. With almost all of the five studied cancers, incidence increased with aging (P value <0.001). The incremental linear trend in the age of patients with lung (P value = 0.008) and colon (P value = 0.004) cancers and the decreasing trend in the age of prostate cancer patients (P value = 0.001) were statistically significant. Conclusion: The incidence of cancer has increased over the past 10 years in both genders and ages. It is suggested that future studies should address the causes and factors behind the increasing incidence of common cancers.